BOOSTING EFL STUDENTS’ GRAMMATICAL COMPETENCE BY IMPLEMENTING RALLYCOACH STRATEGY - Ma’rifatulloh, Sayid (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2016)
This research was aimed to improve students’ grammatical competence in term of parts of speech for the 2nd semester students of English faculty at UNHASY academic year 2015/2016. The instruments used were observation checklists, field notes and the students’ pretest-posttest. The research was conducted through Collaborative Classroom Action Research (CAR) in two cycles. Each cycle consisted of: planning, acting, observing, and reflecting. The result of the study shows that: (1) from the data collected from the observation and field notes, the researcher found out that the students participation in discussing and sharing ideas gradually improved during each meeting; (2) The students’ score in posttest was higher than the score in preliminary test. There were more than 75% students met the criteria of the success. Based on the findings, it can be concluded that RallyCoach strategy is effective to improve the students’ grammatical competence in term of parts of speech and the students’ involvement during the teaching-learning process. Above all, the teacher’s role and the use of appropriate instructional media are very important because those will enhance the students’ motivation in learning English. Keywords: Rally Coach, Grammatical Competence, Parts of Speech